Maximum-likelihood estimation of the 4-parameter generalized weilbull distribution (1992)
Weibull distrlbution is being increasingly employed by researches in tectinology, medicine and other áreas. Its generatlons to four parameters have been proposed, independently, by Stacy (1962) and Cohén (1969) ln this paper, we obtain the maximum-Likelihood estimators of the parameters of generalized Weibull distrlbution (g.w.d). The variance-covariance matrix is derived. We also consider the special coses when the threshold parameter and/or a shape parameter are known.